2002
DOI: 10.1034/j.1399-6576.2002.461011.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid concentrations of atracurium, laudanosine and vecuronium following clinical subarachnoid hemorrhage

Abstract: Significant concentrations of atracurium and laudanosine but not of vecuronium were detected in the CSF of patients during and immediately after intracranial aneurysm surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 32 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…However, there is evidence that patients with an impaired BBB function treated with either of these compounds, present autonomic dysfunction, seizures 39 and neuronal cell death 15. Furthermore, ROC, but not VEC, has been detected in cerebrospinal fluid in patients with subarachnoid haemorrhage who underwent neurosurgery 39,40,41. This finding could be attributed to the fact that ROC is more hydrosoluble than VEC, so it may easily arrives to central nervous system when BBB is damaged 42.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence that patients with an impaired BBB function treated with either of these compounds, present autonomic dysfunction, seizures 39 and neuronal cell death 15. Furthermore, ROC, but not VEC, has been detected in cerebrospinal fluid in patients with subarachnoid haemorrhage who underwent neurosurgery 39,40,41. This finding could be attributed to the fact that ROC is more hydrosoluble than VEC, so it may easily arrives to central nervous system when BBB is damaged 42.…”
Section: Discussionmentioning
confidence: 99%
“…Seizures occur in animals at laudanosine cerebrospinal fluid (CSF) concentrations, approximately 100-1000-fold higher than in clinical conditions during general anesthesia. 15 Moreover, at concentrations comparable to those measured in CSF during and up to eight hours after anesthesia (14-38 ng/mL), namely at nM concentrations, laudanosine can activate a4b2 nACh subtype receptors (nAChRs). 15 Recent research showed that a4b2 receptors represent a primary molecular target for neuroprotection, 16 and activation of a4b2 nAChRs provided neuroprotection against NMDA excitotoxic cascade in a neonatal model.…”
Section: In Replymentioning
confidence: 95%
“…15 Moreover, at concentrations comparable to those measured in CSF during and up to eight hours after anesthesia (14-38 ng/mL), namely at nM concentrations, laudanosine can activate a4b2 nACh subtype receptors (nAChRs). 15 Recent research showed that a4b2 receptors represent a primary molecular target for neuroprotection, 16 and activation of a4b2 nAChRs provided neuroprotection against NMDA excitotoxic cascade in a neonatal model. 17 These finding are also consistent with another recent report in which nicotinic neuroprotection against excitotoxic effects of NMDA is initiated by direct activation of a4b2, or indirectly by inhibition of a7 nAChRs followed by signal transduction involving tyrosine kinases, phospholipid-dependent kinases and mitogen activated kinases.…”
Section: In Replymentioning
confidence: 95%
“…Increased glutamate levels in brain microdialysate are associated with cognitive decline in preclinical models of circulatory arrest. Actracurium and its metabolite laudanosine activate α4β2 nicotinic acetylcholine receptors to levels of normal function in the CNS perioperatively and several hours post- operatively, yielding neuroprotective effects [5,70]. …”
Section: Mechanismsmentioning
confidence: 99%